2023
DOI: 10.3390/antiox12051091
|View full text |Cite
|
Sign up to set email alerts
|

Fermented Whey Ewe’s Milk-Based Fruit Smoothies: Bio-Recycling and Enrichment of Phenolic Compounds and Improvement of Protein Digestibility and Antioxidant Activity

Ali Zein Alabiden Tlais,
Elisabetta Trossolo,
Stefano Tonini
et al.

Abstract: This study aimed to recycle whey milk by-products (protein source) in fruit smoothies (phenolic compounds source) through started-assisted fermentation and delivering sustainable and healthy food formulations capable of providing nutrients that are unavailable due to an unbalanced diet or incorrect eating habits. Five lactic acid bacteria strains were selected as best starters for smoothie production based on the complementarity of pro-technological (kinetics of growth and acidification) traits, exopolysacchar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 77 publications
0
2
0
Order By: Relevance
“…The difference in total phenolic content of different strains was related to the diversity of hydrolase produced by the strains, leading to the difference in hydrolytic ability. ( Tlais et al, 2023 ) explored the influence of fermentation of lactic acid bacteria on the change of phenolic content in sauerkraut and found that lactic acid bacteria metabolized phenolic acid through phenolic acid reductase or decarboxylase, converting caffeic acid into dihydrocaffeic acid and 4-ethyl catechol, ferulic acid into dihydroferulic acid, and caprylic acid into 4-vinylacetopol. 3-hydroxybenzoic acid is converted to catechol, and the derivative exhibits better antioxidant activity than the precursor.…”
Section: Bioactive Ingredients Of Fermented Fruit and Vegetable Juicementioning
confidence: 99%
“…The difference in total phenolic content of different strains was related to the diversity of hydrolase produced by the strains, leading to the difference in hydrolytic ability. ( Tlais et al, 2023 ) explored the influence of fermentation of lactic acid bacteria on the change of phenolic content in sauerkraut and found that lactic acid bacteria metabolized phenolic acid through phenolic acid reductase or decarboxylase, converting caffeic acid into dihydrocaffeic acid and 4-ethyl catechol, ferulic acid into dihydroferulic acid, and caprylic acid into 4-vinylacetopol. 3-hydroxybenzoic acid is converted to catechol, and the derivative exhibits better antioxidant activity than the precursor.…”
Section: Bioactive Ingredients Of Fermented Fruit and Vegetable Juicementioning
confidence: 99%
“…Native MRS broth inoculated with 2% working solution was added with different concentrations (0, 0.25, 0.5, and 1 mg/mL) of LSPC and LPPC, respectively, then maintained at 37 • C for 48 h. The bacterial density was measured at 2 h intervals at 600 nm (OD600) using a 722 N spectrophotometer (Inesa, Shanghai, China). The Gompertz equation was used for modeling growth kinetics according to Tlais et al, with minor modification [23].…”
Section: Growth Experimentsmentioning
confidence: 99%